The classification of employment relationships in Belgium. Issue 3 (September 2019) - Wouters, Mathias
This chapter provides an overview of the characteristics of the Belgian employment contract and, in particular, of the concept of 'subordination'. After having painted a picture of what differentiates an employment contract from a contract for services, it, subsequently, assesses the classification of certain specific examples, such as self-employed persons with only one client. The role of economic dependency in the classification of working relationships is discussed by using these examples. The chapter furthermore emphasises the strong binary divide between employment and self-employment. It goes into more detail on the country's collective bargaining mechanisms for false and genuine self-employed workers. After having described the Belgian take on identifying the 'employing entity', the chapter finishes off by outlining the contemporary debate on the reform of the Belgian classification mechanisms.